Implementation of Patient Safety Program By Nurse at Hospital “X” in Samarinda and Factors Influence - Ramdan, Iwan Muhamad; Setyowati, Dina Lusiana (Kes Mas: Jurnal Fakultas Kesehatan Masyarakat, 2015)
Patient Safety is a system to prevent the occurrence of unexpected events due to actions taken or not even done by medical and non-medical personnel. Nurses are health workers, amounting at most and has a major role in the implementation of patient safety because the profession is to provide services for 24-hour nursing care.  A cross-sectional descriptive study was performed on a total of 77 nurses in “X” Hospital.  The objective of this study was determining the association between education level, work experience, perception of professionalism, knowledge and motivation with implementation of patient safety program. Data collection using a questionnaire and data analysis using Pearson’s product moment correlation and Chi Square test. The results indicated that work experience (p = 0.034), perception of professionalism (p = 0:03), knowledge of patient safety (p = 0.000) and motivation           (p = 0.000) influence to the implementation of patient safety.There was no significant influence of educational level on the implementation of patient safety  program (p = 0.427). To improve the perception and knowledge, hospitals are advised to hold trainings related to patient safety regularly,  and implement reward and funishment system to increase nurse motivation.